Learning episodes in an intercultural virtual exchange: the case of social high-immersion virtual reality - Jauregi-Ondarra, Kristi; Christoforou, Maria; Boglou, Dimitrios (My University, 2022)
Computer-mediated communication tools facilitate international collaboration projects between foreign language learners and peers abroad (O’Dowd, 2018). Social Virtual Reality (VR) applications allow for synchronous interactions and task-based communication in which learners can experience telepresence and immersion and conversate in a foreign language. Based on previous pilot experiences (Jauregi-Ondarra, Gruber, & Canto, 2020, 2021), this Virtual Exchange (VE) project aims to investigate how the specific affordances of Social High-immersion VR (SHiVR) in conjunction with designed tasks influence interaction patterns, and learning episodes. The VE took place between two groups of university students in the Netherlands (N=15) and Cyprus (N=14) through SHiVR in March 2022. The main aims of the tasks were to raise student intercultural awareness, stimulate task-based communication processes using English as a lingua franca and digital pedagogical competences of language education students. Different sources of data were gathered and analysed. In this paper, we describe and present the pedagogical experience and the initial results.
Keywords: Social High-Immersion Virtual Reality; Virtual Exchange; Language-related episodes; Culture-related episodes